2022
DOI: 10.1002/pts.2646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different box preparations on creep performance of corrugated fibreboard boxes subject to constant and cycling relative humidity environments

Abstract: To understand the effect of load and relative humidity (RH) on box creep in cool storage conditions, standard tests are performed. However, these test conditions are oversimplified compared with actual shipping conditions. Our aim is to develop test conditions that more closely mimic those encountered during refrigerated conditions to investigate their influence on creep performance and box lifetime. We compared three box preparations: (i) empty boxes used as a control, (ii) filled boxes, and (iii) boxes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…29 Several researchers have investigated the so-called creep deformation of corrugated board and its components under constant load. [30][31][32][33][34][35][36][37][38][39][40][41] The studies concluded that cyclical changes in humidity generally cause higher creep rates than holding humidity constant. Other studies showed that the creep deformation has three stages: primary, secondary and tertiary (see Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Several researchers have investigated the so-called creep deformation of corrugated board and its components under constant load. [30][31][32][33][34][35][36][37][38][39][40][41] The studies concluded that cyclical changes in humidity generally cause higher creep rates than holding humidity constant. Other studies showed that the creep deformation has three stages: primary, secondary and tertiary (see Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the so‐called creep deformation of corrugated board and its components under constant load 30–41 . The studies concluded that cyclical changes in humidity generally cause higher creep rates than holding humidity constant.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena are strongly affected by environmental conditions (i.e., air humidity) 6 as well as by loading time as folding board boxes can exhibit creep behaviour 7 . Note that variations in air humidity can also promote these creep phenomena 8 …”
Section: Introductionmentioning
confidence: 99%
“…7 Note that variations in air humidity can also promote these creep phenomena. 8 As the compression resistance of the folding board box is related to the buckling behaviour of panels, it greatly depends on the bending stiffness of the folding board. [9][10][11] Designing ribbed plate or shell structures is relevant to improve the moment of inertia of the cross section and accordingly the bending stiffness to weight ratio of materials.…”
mentioning
confidence: 99%